BUNDLE-SHEATH DEFECTIVE, A MUTATION THAT DISRUPTS CELLULAR-DIFFERENTIATION IN MAIZE LEAVES - Langdale, J; Kidner, C (1994)
Post-primordial differentiation events in developing maize leaves produce two photosynthetic cell types (bundle sheath and mesophyll) that are morphologically and biochemically distinct. We have isolated a mutation that disrupts the differentiation of one of these cell types in light-grown leaves. bundle sheath defective 1-mutable 1 (bsd1-m1) is an unstable allele that was induced by transposon mutagenesis. In the bundle sheath cells of bsd1-m1 leaves, chloroplasts differentiate aberrantly and C4 photosynthetic enzymes are absent. The development of mesophyll cells is unaffected. In dark-grown bsd1-m1 seedlings, morphological differentiation of etioplasts is only disrupted in bundle sheath cells but photosynthetic enzyme accumulation patterns are altered in both cell types. These data suggest that, during normal development, the Bsd1 gene directs the morphological differentiation of chloroplasts in a light-independent and bundle sheath cell-specific fashion. In contrast, Bsd1 gene action on photosynthetic gene expression patterns is cell-type independent in the dark (C3 state) but bundle sheath cell-specific in the light (C4 state). Current models hypothesize that C4 photosynthetic differentiation is achieved through a light-induced interaction between bundle sheath and mesophyll cells. Based on the data shown in this paper, we propose that induction of the C4 state restricts Bsd1 gene action to bundle sheath cells.